Prochlorococcus Cells Rely on Microbial Interactions Rather than on Chlorotic Resting Stages To Survive Long-Term Nutrient Starvation - Dalit Roth-Rosenberg (American Society for Microbiology, 2020)
ABSTRACT Many microorganisms produce resting cells with very low metabolic activity that allow them to survive phases of prolonged nutrient or energy stress. In cyanobacteria and some eukaryotic phytoplankton, the production of resting stages is accompanied by a loss of photosynthetic pigments, a process termed chlorosis. Here, we show that a chlorosis-like process occurs under multiple stress conditions in axenic laboratory cultures of Prochlorococcus, the dominant phytoplankton linage in large regions of the oligotrophic ocean and a global key player in ocean biogeochemical cycles. In Prochlorococcus strain MIT9313, chlorotic cells show reduced metabolic activity, measured as C and N uptake by Nanoscale secondary ion mass spectrometry (NanoSIMS). However, unlike many other cyanobacteria, chlorotic Prochlorococcus cells are not viable and do not regrow under axenic conditions when transferred to new media. Nevertheless, cocultures with a heterotrophic bacterium, Alteromonas macleodii HOT1A3, allowed Prochlorococcus to survive nutrient starvation for months. We propose that reliance on co-occurring heterotrophic bacteria, rather than the ability to survive extended starvation as resting cells, underlies the ecological success of Prochlorococcus. IMPORTANCE The ability of microorganisms to withstand long periods of nutrient starvation is key to their survival and success under highly fluctuating conditions that are common in nature. Therefore, one would expect this trait to be prevalent among organisms in the nutrient-poor open ocean. Here, we show that this is not the case for Prochlorococcus, a globally abundant and ecologically important marine cyanobacterium. Instead, Prochlorococcus relies on co-occurring heterotrophic bacteria to survive extended phases of nutrient and light starvation. Our results highlight the power of microbial interactions to drive major biogeochemical cycles in the ocean and elsewhere with consequences at the global scale.